Advanced fracture mechanics and structural integrity - Saxena, A. (Ashok) (Boca Raton : CRC Press, 2019)
Advanced Fracture Mechanics and Structural Integrity is organized to cover quantitative descriptions of crack growth and fracture phenomena. The mechanics of fracture are explained, emphasizing elastic-plastic and time-dependent fracture mechanics. Applications are presented, using examples from power generation, aerospace, marine, and chemical industries, with focus on predicting the remaining life of structural components and advanced testing metods for structural materials. Numerous examples and end-of-chapter problems are provided, along with references to encourage further study.The book is written for use in an advanced graduate course on fracture mechanics or structural integrity.
3.5 Summary3.6 References; 3.7 Exercise Problems; Appendix 3.1; 4. Crack Growth Resistance Curves and Measures of Fracture Toughness; 4.1 Fracture Parameters under Elastic-Plastic Loading; 4.2 Experimental Methods for Determining Stable Crack Growth and Fracture; 4.2.1 Overall Test Method; 4.2.2 Test Specimen Geometries and Preparation; 4.2.3 Loading Apparatus and Displacement Gauges; 4.2.4 Crack Length Measurement; 4.2.5 Final Loading of the Specimen and Post-test Measurements; 4.2.6 Data Analysis and Qualification; 4.3 Summary; 4.4 References; 4.5 Exercise Problems
OCLC-licensed vendor bibliographic record.
Keywords: Fracture mechanics; TECHNOLOGY & ENGINEERING / Engineering (General); TECHNOLOGY & ENGINEERING / Reference; TECHNOLOGY / Engineering / Mechanical; TECHNOLOGY / Engineering / Civil; TECHNOLOGY / Material Science